PEMANFAATAN RUANG TERBUKA SEBAGAI RUANG TUNGGU RAMAH PENUMPANG (STUDI KASUS: RUANG TERBUKA FLY OVER KUNINGAN, JAKARTA) - Dody Kurniawan (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2023)
Open space in Jakarta is also now increasingly reduced because of the many infrastructure developments, such as toll roads, highways, and others. Flyover construction creates open spaces that have not been used optimally. One of them is open space at the Transjakarta shelter in Kuningan Barat, which is located below the fly over. The open space has the potential to be used as a waiting room at passenger-friendly Transjakarta shelter. The open space has the potential to be used as a waiting room at passenger-friendly Transjakarta shelter. Besides being friendly to passengers, open space must also be able to add facilities to the needs of the users of the shelter. A descriptive method will be used to carried out to make a description, description systematically factually and accurately regarding the facts, characteristics and relationships between the phenomena investigated. This description is obtained through field observations, interviews and data from relevant agencies. The method of the approach taken to achieve the predetermined goals is the Identification of Design Norms; Identification of Comparative Studies and Identification of Potentials and Problems. The results of this study are in the form of a redesign of the sidewalk which functions as a Transit Pedestrian so that it can accommodate pedestrian needs and become a means of transit. This research is expected to provide input regarding the concept of using open space as a passenger-friendly waiting room at a Transjakarta shelter.Â